2020
DOI: 10.3390/ani10081305
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, Mortality Causes, and Pathological Findings in European Hedgehogs (Erinaceus europaeus, Linnaeus 1758): A Seventeen Year Retrospective Analysis in the North of Portugal

Abstract: This study aimed to analyze the admission causes, outcomes, primary causes of death, and main lesions observed in the post mortem examinations of Western European hedgehogs, Erinaceus europaeus (Linnaeus, 1758), in the north of Portugal. The data were obtained by consulting the records from the two main wildlife rehabilitation centers located in the north of Portugal (Wildlife Rehabilitation Centre of Parque Biologico de Gaia and the Wildlife Rehabilitation Centre of the University of Trás-os-Montes and Alto D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…Injured hedgehogs are frequently admitted to hedgehog rehabilitation centres with different types of cuts and injuries. Some injuries are consistent with known risks to hedgehogs in the form of garden trimmers and dog bites [ 11 , 12 , 13 ]. However, although not rigorously quantified, a concern has arisen in several European countries that an increasing number of cases may have been caused by robotic lawn mowers.…”
Section: Introductionsupporting
confidence: 67%
“…Injured hedgehogs are frequently admitted to hedgehog rehabilitation centres with different types of cuts and injuries. Some injuries are consistent with known risks to hedgehogs in the form of garden trimmers and dog bites [ 11 , 12 , 13 ]. However, although not rigorously quantified, a concern has arisen in several European countries that an increasing number of cases may have been caused by robotic lawn mowers.…”
Section: Introductionsupporting
confidence: 67%
“…According to Bearman-Brown et al [ 32 ], the optimum weight of hedgehogs before hibernation is at least 600 g. The issue of underweight hedgehogs not surviving winter is well known to the public, which is why hedgehogs are often brought to rescue centers in this season. Similarly, Garcês et al [ 33 ] reported the most common reason for admission in Portugal to be weakness (30.7%). Hedgehogs may go through periods where they are unsuccessful in finding enough food.…”
Section: Discussionmentioning
confidence: 84%
“…They found the highest number of admissions of European hedgehogs from July to December. In Portugal, 740 western hedgehogs were admitted to two rescue centers [ 33 ] in the period from 2002 to 2019. There, besides the high admission rates in the summer, an increased intake was also found in the spring months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,9,11,[21][22][23]). Single species studies are also common [15,[24][25][26][27][28] including those for species with a threatened conservation status [2,13,29,30]). Wildlife rehabilitation data have also been used more broadly for disease surveillance [24,[31][32][33][34], and in animal health science [22,35,36].…”
Section: Introductionmentioning
confidence: 99%